Analisis Implementasi Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) II Kabupaten Semarang (Studi Kasus Desa Timpik Kecamatan Susukan) - Selin Nur Riski; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
Since the PAMSIMAS program was implemented in Semarang Regency from PAMSIMAS I (2008-2012) to PAMSIMAS II (2013-2015) program, there are 93 PAMSIMAS facilities in the village from the total number of villages in Semarang Regency. However, until 2015, there was 1 non functioning village and 6 partially functiong villages in the PAMSIMAS program in Semarang Regency. One of the villages is Timpik Village in Susukan Sub-district. The aim of this study is to describe how the implementation of PAMSIMAS, the form of PAMSIMAS program, the form of implemented community empowerment, and solutions to overcome problems that arise in the Timpik Village. The theoretical approach used in this research is the Bottom-Up policy implementation approach which emphasizes the importance of considering two important aspects in the implementation of a policy, such as lower level bureaucrats and policy target group. This research used qualitative approch as its main aproach. The process of collecting data in this study used several techniques of observation, interview and documentation. In testing the validity and reliability of data, this research used triangulation technique of data source. The results showed that in the implementation, all elements that play a role in the PAMSIMAS program managements institutions and administrators both from the village and dsitrict have performed their duties and functions well so that peple get various benefits, especially in the field of access to drinking ater from them. However, there are still several obstacles which make this PAMSIMAS program not always run smoothly. The recommendation of this research is that the village level implementor should be more visionary and innovative in the future in solving the existing obstacles. In addition, it is expected that the community will participate and supprt in the development related to the continuations of PAMSIMAS program and continue to innovate in developing the programs that have been run before. Keywords : Policy Implementation, Community Empowerment, Community-Based Water Supply and Sanitation Program.